New Topical Drug Delivery System Pharmaceutical Organogel: A Review - Sharma, Jaya; Agrawal, Dilip; Sharma, Ashok Kumar; Khandelwal, Mohit; Aman, Shaneza (Asian Journal of Pharmaceutical Research and Development, 2022)
A simple working definition of this term'Gel' is a soft, durable or solid material,containing both solids and liquid parts, where the solid part(gelator) exists as amesh / network of aggregates, viz immobilize part of the liquid,a strong network prevents the liquid from leaking flow, especially by local pressure. The gel is called a hydrogel or Organogel depending on the type liquid component: water in hydrogel and a living solvent in organogels .Organogels have been discovered as a multipurpose tool in pharmaceuticals for topical as well as transdermal delivery of various drugs. They are semisolid classifications consists of apolar phase and a solid phase. Gels are form through the mechanism of entrapment of a polar segment into the three-dimensional networked assembly of solid phase. Apolar phase is inculded as a solvent such as isopropyl palmitate, isopropyl myristate etc.an organogelator such as sorbiatanmonostearte, lecithin etc. are consist by solid phase Organogel, non-crystalline, nonglassythermoreversible (thermoplastic)solid materials and viscoelastic system,can be considered semi-solid an immobilized preparation external apholar phase. Apholar the section closes between spaces of a three-dimensional network a structure built due to physical condition negotiation between collectors compound properties considered as gelators. Generally, these programs are supported in structurant integration molecules .These systems are good transporter for both hydrophilic and lipophilic therapeutic agents. The present review describes a number of important properties of organogel, different types of organogel based on organogelator, method of preparation and various applications in pharmaceuticals.